Levels of pro-inflammatory (TNF-α and IL -6) and anti-inflammatory (IL -10 and IL- 4) interleukins in ocular herpes patients with frequent and infrequent recurrences - N. I. Khramenko; T. B. Gaidamaka; G. I. Drozhzhyna; L. N. Velychko (Ukrainian Society of Ophthalmologists, 2020)
Background: Herpes simplex virus ocular infection is the major cause of corneal blindness in developed countries. The methods used for the treatment of recurrent herpes infections give only temporary remission, and the results of studies on prevention and prediction of the course of the disease are contradictory, which makes management of these infections not only medically, but also socially important. The mechanism of recurrence of herpetic stromal keratitis (HSK) infection has not been clearly understood, since the disease involves complex pathophysiological mechanisms and immune factors (including cytokines) are complexly interrelated in the pathogenesis. Purpose: To assess serum levels of proinflammatory cytokines (TNF-α and IL-6) and anti-inflammatory cytokines (IL-10 and IL-4) in ocular HSK patients with frequent and infrequent recurrences during remission and recurrence. Material and Methods: Thirty-three in-patients (15 patients and 18 patients experiencing less than and more than one recurrence annually, respectively) treated for recurrent HSK at the Department of Corneal Disorders of the Filatov Institute were included in the study. Serum IL-4, IL-6, IL-10 and TNF-α levels were determined using enzyme-linked immunosorbent assay (ELISA) kits from Vektor-Best (Novosibirsk, Russia) according to the manufacturer's instruction. Photometric measurements were performed on an ELISA plate reader (Stat Fax 2100, Awareness Technologies Inc, Palm City, FL). Reference normal values were taken from the manufacturer's instructions. Results: We found that the mean serum TNF-α level in patients with infrequent recurrences and in those with frequent recurrences during remission was 2.6 times and 4 times, respectively, higher, and during recurrence, 5.6 times higher, compared to normal values, which is likely to indicate a subclinical inflammatory process. Both in patients with infrequent recurrences and in those with frequent recurrences of keratitis, the mean serum TNF-α level was 50% higher during recurrence than during remission. The mean serum IL-6 level during remission was comparable to, and during recurrence was 3 times higher than the norm, with no significant difference between patients with infrequent and frequent recurrences. Serum IL-4 levels in patients with infrequent and frequent recurrences were 8.5 times and 22.5 times, respectively, higher than reference values. During recurrence, the mean serum IL-4 level in patients with frequent recurrences was 39% higher than in those with infrequent recurrences. No significant difference was observed in serum IL-10 level between remission and recurrence for patients with infrequent recurrences, with a mean value being 24% higher than reference values. The mean serum IL-10 level (for recurrence and remission) in patients with frequent recurrences was 74% higher than for patients with infrequent recurrences (p = 0.01), and two times higher than reference values. Conclusion: HSK in patients with frequent recurrences was characterized by the pattern of regulation of cytokine expression, with decreased expression of TNF-α and increased expression of pro-inflammatory (IL-6) and anti-inflammatory (IL-10 and IL-4) interleukins, which might reflect a mechanism of autoimmune response in such a course of herpetic keratitis.